The Effect of Gamified and Interactive Features of the British Council Learn English Website on Students’ Vocabulary Acquisition - Resti Andina Putri; Zulia Chasanah; Juita Triana (Universitas Islam Negeri Palopo, 2026)
The acquisition of vocabulary tends to be a difficult process in Indonesian EFL classrooms, specifically in vocational high schools where conventional instruction often fails to sustain learner engagement. The British Council LearnEnglish website was selected as the instructional medium due to its unique integration of multiple gamified and interactive features — including vocabulary games, image-based matching, and audio pronunciation exercises — within a single freely accessible platform, distinguishing it from single-feature tools. This research examined the effect of the gamified and interactive features of the British Council LearnEnglish website toward the English vocabulary acquisition among tenth-grade students at Vocational High School, Indonesia. The research employed a quasi-experimental pre-test and post-test control group design, consisting of 60 participants equally separated into a experimental group (n = 30) and a control group (n = 30). Vocabulary training was delivered to the experimental group through the British Council LearnEnglish website across four treatment sessions, while conventional training addressing the identical vocabulary topics was provided to the control group. To collect the data, the researcher employed a 40-item multiple-choice vocabulary test. The data were then analyzed using paired-samples t-test, independent-samples t-test, and N-Gain score analysis. Findings showed a statistically meaningful enhancement in the experimental group, t(29) = -12.412, p < .001, Cohen's d = 2.27, and a significant between-group difference, t(58) = -4.810, p < .001, Cohen's d = 1.24. The experimental group succeeded in a moderate N-Gain (.5958), while the control group achieved a low N-Gain (.2313). These findings confirm that the platform's gamified and interactive features substantially and meaningfully enhance students' vocabulary acquisition, contributing empirical evidence on feature-based digital vocabulary learning in the underrepresented Indonesian vocational high school context.